2017
DOI: 10.3389/fphys.2017.00925
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride Alters Klk4 Expression in Maturation Ameloblasts through Androgen and Progesterone Receptor Signaling

Abstract: Fluorosed maturation stage enamel is hypomineralized in part due to a delay in the removal of matrix proteins to inhibit final crystal growth. The delay in protein removal is likely related to reduced expression of kallikrein-related peptidase 4 (KLK4), resulting in a reduced matrix proteinase activity that found in fluorosed enamel. Klk4 transcription is known to be regulated in other cell types by androgen receptor (AR) and progesterone receptors (PR). In this study, we determined the possible role of fluori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 53 publications
(78 reference statements)
0
2
0
1
Order By: Relevance
“…However, our finding that fluoride was associated specifically with the WBC subtypes of neutrophils and monocytes, while not affecting lymphocytes, eosinophils and basophils, indicates a specific effect of fluoride in enhancing inflammation. In animal models, fluoride in drinking water has been shown to increase activation of NF-kB in cells and organs throughout the body, including ameloblasts [ 34 ] and liver [ 35 ]. NF-kB has a critical role in mediating the inflammatory response [ 36 ], and our report of an association between plasma fluoride concentrations and WBC counts in children suggests that findings of fluoride associated inflammation in animal models, may also be relevant to human populations.…”
Section: Discussionmentioning
confidence: 99%
“…However, our finding that fluoride was associated specifically with the WBC subtypes of neutrophils and monocytes, while not affecting lymphocytes, eosinophils and basophils, indicates a specific effect of fluoride in enhancing inflammation. In animal models, fluoride in drinking water has been shown to increase activation of NF-kB in cells and organs throughout the body, including ameloblasts [ 34 ] and liver [ 35 ]. NF-kB has a critical role in mediating the inflammatory response [ 36 ], and our report of an association between plasma fluoride concentrations and WBC counts in children suggests that findings of fluoride associated inflammation in animal models, may also be relevant to human populations.…”
Section: Discussionmentioning
confidence: 99%
“…Sodium fluoride has also been reported to inhibit AR mRNA expression in Sertoli cells in mice, reducing AR protein and gene expression in the testis, therefore, negatively affecting male fertility (Huang et al, 2008). The decrease in AR transcriptional activity observed in the current study may be due to the effect of fluoride on 90-kDa heat-shock protein (HSP90) which may reduce transforming growth factor receptor-2 (TGFR-2) levels, and suppress TGF-β signalling activity, via upregulated cyclins D1 (CCND1) (Knudsen, et al, 1999;Le et al, 2017). Previous studies have also identified that the plastic leachate BPA can directly bind to the AR acting as an antagonist of the AR via inhibiting the actions of endogenous androgens and transcription of AR target genes at concentrations Frontiers in Toxicology frontiersin.org above and below the total daily intake (4 μg/kg body weight/day for a 70 kg person) (Lee et al, 2003;Xu et al, 2005;Sun et al, 2006;Bonefeld-Jørgensen et al, 2007;Teng et al, 2013;Ma et al, 2019).…”
Section: Categorymentioning
confidence: 91%
“…L'exposition au fluor a ainsi été associée à des effets dépassant le cadre buccal et les tissus minéralisés, dont des effets neurotoxiques et une diminution du quotient intellectuel [33,34], des perturbations de l'axe androgénique [35] (le fluor est répertorié comme un PE dans la TEDX List), et une augmentation des processus inflammatoires [36]. L'implication des récepteurs des hormones stéroïdiennes (progestérone et androgènes) dans les mécanismes d'action du fluor sur les améloblastes [37] laisse ainsi suspecter de fortes interactions entre fluor et PE. D'ailleurs, le fluor et le BPA peuvent avoir des effets complémentaires et additionnels comme perturbateurs de l'amélogénèse [38].…”
Section: Référencesunclassified